EXTH-58. INHIBITION OF DNA TOPOISOMERASE 1 AND POLY(ADP-RIBOSE) POLYMERASE SYNERGISTICALLY INDUCES CELL DEATH IN GLIOBLASTOMA WITH PTEN LOSS. (11th November 2019) - Butler, Madison; Su, Yu-Ting; Hwang, Lee; Marzi, Laetitia; Gilbert, Mark; Pommier, Yves; Wu, Jing
Abstract: BACKGROUND: Glioblastoma is known for its aggressive behavior and resistance to most available treatments. Topoisomerase 1 (Top1) functions by relaxing DNA supercoiling to facilitate replication. The novel Top1 inhibitor, LMP400, traps the enzyme and prevents its normal function, particularly in highly proliferative cells, resulting in DNA damage. Poly(ADP-ribose) polymerase (PARP) is involved in DNA repair responses triggered by Top1 inhibition. Phosphatase and tensin homolog (PTEN) loss, a frequent occurrence in glioblastoma, promotes DNA damage repair deficiency. We hypothesize that PTEN loss presents a vulnerability to combined induction of DNA damage and inhibition of repair mechanisms. METHODS: Human glioblastoma cells were treated with LMP400 and/or Olaparib, a PARP inhibitor. Effects on cell proliferation and cell death were determined using a Beckman Coulter cell viability analyzer and colony formation assays. Synergism was calculated using COMPUSYN software. Cell cycle analysis was performed by FACS with EdU/DAPI staining, and Western blotting of lysate from drug-treated cells was performed to explore mechanisms of cytotoxicity. RESULTS: LMP400 inhibited cell proliferation with an EC50 of 8.0 nM in U251 cells, and combination of LMP400 and Olaparib had a synergistic cytotoxic effect. Combination treatment enhanced activation of ATM-Chk2 and ATR-Chk1 pathways involved in DNA damage response signaling and increased S phase arrest. Increased protein expression of gamma-H2AX, cleaved caspase 3, and cleaved PARP was observed in combination-treated cells compared to single agents. Cell viability assays using isogenic glioblastoma cell lines with and without PTEN indicate that PTEN loss increases sensitivity to combination treatment. CONCLUSION: Our results suggest that LMP400 and Olaparib combined treatment synergistically induces glioblastoma cell death, partially through inducing DNA damage, cell cycle arrest, and apoptosis. Mechanistic studies to investigate this vulnerability in glioblastoma with PTEN loss are ongoing. These results may lead to an effective personalized therapy for a molecularly defined subset of glioblastoma patients.